2010
DOI: 10.1063/1.3298857
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrogen bonding on the diffusion of water in n-alkanes and n-alcohols measured with a novel single microdroplet method

Abstract: While the Stokes-Einstein ͑SE͒ equation predicts that the diffusion coefficient of a solute will be inversely proportional to the viscosity of the solvent, this relation is commonly known to fail for solutes, which are the same size or smaller than the solvent. Multiple researchers have reported that for small solutes, the diffusion coefficient is inversely proportional to the viscosity to a fractional power, and that solutes actually diffuse faster than SE predicts. For other solvent systems, attractive solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
114
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 39 publications
13
114
0
Order By: Relevance
“…In fact the NMR-derived molecular diffusion coefficients show no special variation close to the consolute point. This is in agreement with Su et al (2010) who, for a range of water-alcohol (C 4 -C 16 ) mixtures, found no evidence for solute-solvent cluster diffusion.…”
Section: T [1c]supporting
confidence: 92%
“…In fact the NMR-derived molecular diffusion coefficients show no special variation close to the consolute point. This is in agreement with Su et al (2010) who, for a range of water-alcohol (C 4 -C 16 ) mixtures, found no evidence for solute-solvent cluster diffusion.…”
Section: T [1c]supporting
confidence: 92%
“…For microfluidics, this time has an inverse relation to the velocity of the fluid in the microchannel and is directly proportional to the length of that channel. Thus, calculations of the time for dissolution are readily obtained from the EP model for the dissolution of microparticles as done previously [2,4,27,30]. The time, tD, for a spherical microparticle of Ibp to dissolve in infinite medium is given by the following equation,…”
Section: New Measure Of Ibp Diffusion Coefficient and Dissolution Timmentioning
confidence: 99%
“…It has now become a highly versatile experimental setup that allows a wide variety of studies at microscopic interfaces and with single-and pairs-of microparticles. Among other applications, the technique has been established for studying solvent dissolution, measuring fundamental properties such as diffusion coefficients and solubilities of the dissolving liquids [4,27,30], and for evaluating the phase separation, precipitation of droplets containing different solutes upon solvent loss, such as the micro-glassification of proteins by fast removal of water into water-imbibing solvents like octanol [3,31], and drug-containing polymer microspheres by removal of the organic solvent into water [28,29]. It is this last application that has motivated and guided the current studies with poly(lactic-co-glycolic acid) (PLGA) microparticles containing Ibuprofen [34].…”
Section: The Micropipette Techniquementioning
confidence: 99%
See 2 more Smart Citations